Nem tudo que reluz é ouro: Dos símbolos coloniais da Serra do Lenheiro para sua percepção ambiental - Santos, Maisa dos (2024)
The studies aiming to understand the relationship between the environment and humans have been increasingly gaining prominence in academic research. Environmental perception is considered one of the viable paths to comprehend the connection between humans and the environment in a given space. For this reason, environmental perception serves as the theoretical foundation for the construction of this research, with the overall objective of understanding the meanings attributed to cultural elements comprising the landscape of Serra do Lenheiro, São João del-Rei (MG). The specific objectives include: (1) describing symbolic elements and their meanings in Serra do Lenheiro; (2) analyzing teachers' perceptions of Serra do Lenheiro; (3) identifying teachers' aspirations regarding the implementation of an Environmental Education project in the school. To achieve the outlined objectives, the chosen method is phenomenology, complemented by concepts from Humanistic Cultural Geography for the geographical interpretation of the selected analytical category (Place and Landscape). In the pursuit of understanding the Place in Serra as a lived environment, recognized as a symbol laden with meanings, the research explores the interaction between the local population and the elements of Serra, advocating it as a symbol rich in meanings, stories, beliefs, and legends in the landscape of the aforementioned municipality. To structure the dissertation and fulfill the established objectives, it is organized into five section. The Section II serves as the theoretical framework, presenting the research analysis concepts: Place and Landscape. In Section III applies the concept of polyvocality (Corrêa, 2007) to the landscape of Serra do Lenheiro, while Section IV explores the concept of Place in the mountainous landscape of Lenheiro through group interaction. Finally, the Section V presents the methodology of the semi-structured interview applied to participants, focusing on teachers from the Secondary School of Professor Iago Pimentel and the school's pedagogical coordinator. The aim is to examine the perceptions, attitudes, and values that educators hold regarding Serra do Lenheiro.